2010
DOI: 10.20533/iji.1742.4712.2010.0033
|View full text |Cite
|
Sign up to set email alerts
|

ProVerif Analysis of the ZRTP Protocol

Abstract: When some agents want to communicate through a media stream (for example voice or video), the Real Time Protocol (RTP) is used. This protocol does not provide encryption, so it is necessary to use Secure RTP (SRTP) to secure the communication. In order for this to work, the agents need to agree on key material and ZRTP provides them with a procedure to perform this task: it is a key agreement protocol, which relies on a Diffie-Hellman exchange to generate SRTP session parameters, providing confidentiality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…There have been several studies about security verification of standardized cryptographic protocols with formal methods. ProVerif and CryptoVerif [18] have been used to verify other standardized protocols such as ZRTP [19], SN-MPv3 [20], mutual authentication protocol for GSM [21], LTE [22], OpenID Connect protocol [23], and others. Cremers and Horvat [8] verified 30 key exchange protocols standardized in ISO/IEC 11770-2 [9] and ISO/IEC 11770-3 [10] with automated security verification tool Scyther [11], and found some spoofing attacks.…”
Section: Related Workmentioning
confidence: 99%
“…There have been several studies about security verification of standardized cryptographic protocols with formal methods. ProVerif and CryptoVerif [18] have been used to verify other standardized protocols such as ZRTP [19], SN-MPv3 [20], mutual authentication protocol for GSM [21], LTE [22], OpenID Connect protocol [23], and others. Cremers and Horvat [8] verified 30 key exchange protocols standardized in ISO/IEC 11770-2 [9] and ISO/IEC 11770-3 [10] with automated security verification tool Scyther [11], and found some spoofing attacks.…”
Section: Related Workmentioning
confidence: 99%
“…There have been several studies about security verification of standardized cryptographic protocols with formal methods. ProVerif and CryptoVerif [17] have been used to verify other standardized protocols such as ZRTP [18], SNMPv3 [19], mutual authentication protocol for GSM [20], LTE [21], OpenID Connect protocol [22], and others. Cremers and Horvat [7] verified 30 key exchange protocols standardized in ISO/IEC 11770-2 [8] and ISO/IEC 11770-3 [9] with automated security verification tool Scyther [10], and found some spoofing attacks.…”
Section: Related Workmentioning
confidence: 99%
“…ZRTP has been verified formally by Bresciani et al [4][5][6]. It was shown that it is a secure key agreement protocol under the Dolev-Yao model.…”
Section: Related Workmentioning
confidence: 99%
“…Before its standardization, ZRTP has been formally verified by Bresciani et al [6]. The authors analyzed the protocol with the "correctly verified SAS" assumption.…”
Section: Introductionmentioning
confidence: 99%